Cheney Lake Watershed: Assessing the Impact of Implementing Conservation Practices in the Cheney Lake Watershed - Devlin, Daniel; Mankin, Kyle; Selfa, Teresa; Nelson, Nathan; Barnes, Philip; Miller, Howard; French, Lisa; Frees, Lyle; Langemeier, Michael (My University, 2008)
Research on the impact of conservation practices in the Cheney Lake Watershed by the city of Wichita, KS.
EP158_2008-11
Keywords: EP158; Environment and Natural Resources; EP